In Vivo Outcome of Homology-Directed Repair at the HBB Gene in HSC Using Alternative Donor Template Delivery Methods - Sowmya Pattabhi; Samantha N. Lotti; Mason P. Berger; Swati Singh; Christopher T. Lux; Kyle Jacoby; Calvin Lee; Olivier Negre; Andrew M. Scharenberg; David J. Rawlings (Elsevier, 2019)
Gene editing following designer nuclease cleavage in the presence of a DNA donor template can revert mutations in disease-causing genes. For optimal benefit, reversion of the point mutation in HBB leading to sickle cell disease (SCD) would permit precise homology-directed repair (HDR) while concurrently limiting on-target non-homologous end joining (NHEJ)-based HBB disruption. In this study, we directly compared the relative efficiency of co-delivery of a novel CRISPR/Cas9 ribonucleoprotein targeting HBB in association with recombinant adeno-associated virus 6 (rAAV6) versus single-stranded oligodeoxynucleotides (ssODNs) to introduce the sickle mutation (GTC or GTG; encoding E6V) or a silent change (GAA; encoding E6optE) in human CD34+ mobilized peripheral blood stem cells (mPBSCs) derived from healthy donors. In vitro, rAAV6 outperformed ssODN donor template delivery and mediated greater HDR correction, leading to both higher HDR rates and a higher HDR:NHEJ ratio. In contrast, at 12-14 weeks post-transplant into recipient, immunodeficient, NOD, B6, SCID Il2rγ−/− Kit(W41/W41) (NBSGW) mice, a ∼6-fold higher proportion of ssODN-modified cells persisted in vivo compared to recipients of rAAV6-modified mPBSCs. Together, our findings highlight that methodology for donor template delivery markedly impacts long-term persistence of HBB gene-modified mPBSCs, and they suggest that the ssODN platform is likely to be most amenable to direct clinical translation. Keywords: sickle cell disease, gene editing, rAAV6, ssODN, homology-directed repair, Crispr/Cas9, hemoglobin disorders, NHEJ versus HDR, in vivo engraftment, NBSGW41 mice, CD34, hematopoietic stem cells, stem cell cures